The Effect of Digital Content Creativity and Artificial Intelligence Utilization on Consumer Purchase Intention on TikTok: Consumer Trust as a Moderator - Nurjanah, Siti; Darnis, Rahmi (Dinasti Publisher, 2026)
This study aims to investigate the influence of digital content creativity and the use of Artificial Intelligence (AI) on consumer purchase intent on TikTok, with consumer trust serving as a moderating variable in the relationship among these variables. Employing a quantitative approach, this research utilizes Structural Equation Modeling Partial Least Squares (SEM-PLS) for data analysis Data collection was conducted by distributing an online questionnaire to 130 respondents who met the study’s criteria active TikTok users who had made a purchase on TikTok Shop. The findings reveal that digital content creativity, AI utilization, and consumer trust each exert a positive and significant influence on consumer purchase intention. Furthermore, consumer trust is proven to positively moderate the effect of AI utilization on purchase intention; however, it does not significantly moderate the influence of digital content creativity on purchase intention. These findings highlight that digital content creativity, AI utilization, and consumer trust are critical factors in enhancing consumer purchase intention on the TikTok platform. The findings of this study are expected to serve as a basis for business owners to develop more effective digital marketing strategies.